Investigation of the genetic diversity of jewel orchid in Vietnam using RAPD and ISSR markers (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tran TKP, Pham MH, Trinh TH, Widiarsih S, Ho VT. 2022. Investigation of the genetic diversity of jewel orchid in Vietnam using RAPD and ISSR markers. Biodiversitas 23: 4816-4825. Jewel orchid is a general name for several genera belonging to the Orchidaceae family, namely Anoectochilus, Doddinia, Goodyera, Ludisia, and Macodes. These plants are generally used as medicinal herbal for common diseases in Vietnam. Due to over-exploitation, the natural resources of jewel orchids are gradually depleted. Therefore, genetic resource research for proper development of this medicinal plant is necessary. This study aimed to investigate the genetic diversity of jewel orchids in Vietnam using RAPD and ISSR markers to provide basic data conservation of genetic resources and the development of this medicinal plant. A total of 20 jewel orchid samples were genetically characterized by using 10 RAPD and 10 ISSR primers. The amplified bands were binary coded and used to construct phylogenetic trees with NTSYSpc 2.1 software. Each RAPD primer produced 5-11 bands with an average of 8.0, and similarity coefficients ranged from 0.52 to 0.81. Each ISSR primer produced 5-10 bands with an average of 7.6, and the similarity coefficients ranged from 0.54 to 0.87. Combined RAPD and ISSR markers produced similarity coefficients ranging from 0.53 to 0.83. Based on the PIC values, the primers used by both markers are highly informative. However, the topology of cluster analysis of 20 jewel orchid accessions does not correspond to the taxa studied. The findings could be potential to employ in future classification, conservation, and development of this plant.
Keywords: Genetic diversity, ISSR, jewel orchid, molecular markers, RAPD